EXAMINING GENDER DIFFERENCES IN STUDENTS’ CONCEPTUAL CHANGE THROUGH RADEC MODEL ASSISTED BY VIRTUAL LABORATORY - Henni Riyanti; Wahyu Sopandi; Dadi Mulyadi; Muslim (Universitas Majalengka, 2026)
Conceptual change is a fundamental goal of science learning, particularly in elementary teacher education, where preservice teachers’ understanding of scientific concepts directly influences their future instructional practices. This study aimed to examine the relationship between gender and students’ conceptual change in science learning implemented through the RADEC (Read–Answer–Discuss–Explain–Create) learning model assisted by a virtual laboratory. A correlational research design was employed involving first-semester students of the Elementary School Teacher Education (PGSD) program at a private university in South Sumatra. Data were collected using a four-tier conceptual change test on magnetism concepts. The sample comprised 39 students selected through random sampling, including 34 female and 5 male students. Students’ conceptual change was analyzed using normalized gain (N-gain), while the relationship between gender and conceptual change was examined using Pearson correlation analysis with SPSS version 26. The results indicated a statistically significant relationship between gender and students’ conceptual change in the implementation of the RADEC model assisted by a virtual laboratory (r = 0.190, p < 0.05). However, the strength of the correlation is weak, indicating that gender is not a major determinant of students’ conceptual development. Future research is recommended to explore additional factors influencing conceptual change, including prior knowledge, learning motivation, and student engagement, to better understand the determinants of students’ conceptual development.